Studies on the ecology and molecular biology of transferable drug resistance factors in coliform bacteria - Marcos, David (Rhodes University, Faculty of Science, Botany Department, 1973)
From Introduction: It was as early as 1904 that Paul Ehrlich propounded the idea of a "magic bullet" . This "magic bullet" , or chemotherapeutic agent, as he also called it, had to meet certain requirements: (a) a high activity against pathogenic micro-organisms; (b) easy absorption by the body; (c) activity in the presence of body fluids and tissue; (d) a low degree of toxicity; (e) must not allow the development of resistant micro-organisms. The discovery of the sulphonamide, Prentosil, by Domagk in 1935 was one of the initial steps in the search for this "magic bullet" . This, together with the production and purification of the antibiotics penicillin, by Fleming, Florey and Chain in 1942 and streptomycin, by Waksman in 1943, heralded a new era in the fight against bacterial infections. The majority of modern antibacterial agents have to a large extent met the requirements of Ehrlich's 'magic bullet" . They have however failed to prevent the development of resistant bacterial strains. This has been particularly noticeable in the past twenty years since the sudden emergence of multiple-resistant bacteria, many of which can transfer to several drugs in one step by a process of conjugation. This phenomenon which has serious medical implications has prompted numerous studies on the origin, epidemiology, biochemistry and genetics of transferable drug resistance.
Keywords: Enterobacteriaceae; Molecular biology; Microbial ecology; Bacteria -- Ecology; Ecology